Language Endangement and Vitality of the Bidayuh Language - Norahim, Norazuna (Centre for Language Studies, Universiti Malaysia Sarawak ., 2014)
Objective is to address the subject of language endangerment and language vitality in the contexts of Sarawak with a particular focus on the Bidayuh speech community.